Treating nontuberculous mycobacteria in children with cystic fibrosis: a multicentre retrospective study. Issue 5 (5th November 2021) - Saint, Gemma L; Thomas, Matthew F; Zainal Abidin, Noreen; Langley, Ross John; Brodlie, Malcolm; McNamara, Paul
Abstract : Background: Respiratory infection with nontuberculous mycobacteria (NTM) in children with cystic fibrosis (CF) has increased in prevalence. The condition is difficult to diagnose and treatments are complex with limited evidence to guide practice. This study describes the approaches to diagnosis, management and consequences of treatment in a multicentre cohort of children with CF in the UK. Methods: Retrospective data were collected from 11 CF specialist centres from patients less than 17 years old, treated for NTM infection between 2006 and 2017. Descriptive statistics were used to describe the clinical characteristics of children treated. Treatment regimens, adverse events and success of treatment, with respect to lung function and culture conversion, were evaluated. Results: Data from 70 patients treated for NTM pulmonary disease were collated (60 Mycobacterium abscessus complex (MABSC); 10 M . avium complex (MAC)). Older age and previous diagnosis of allergic bronchopulmonary aspergillosis were all significantly associated with NTM. There was a wide variance in drug choice and side effects were reported with all agents. NTM eradication occurred in 80% of patients with MAC and 48% with MABSC, with variable outcomes on lung function. Conclusions: Diagnosis and treatment of NTM infection in children with CF is challenging. Treatment success is not guaranteed, particularly for MABSC. Large clinical trials are urgently required to evaluate treatment regimes and their suitability and efficacy in children. Abstract : Data from 11 cystic fibrosis centres in UK with clinical information on 70 subjects examining nontuberculous mycobacterium (NTM) were collated (60 Mycobacterium abscessus complex (MABSC) 10 M. avium complex (MAC)). Older age and previous diagnosis of allergic bronchopulmonary aspergillosis were all with NTM. There was a wide variance in drug choice and side effects were reported with all agents. NTM eradication occurred in 80% of patients with MAC and 48% with MABSC, with variable outcomes on lung function. Large multi centre studies are required.